Visual Outcomes and Patient Satisfaction After Bilateral Refractive Lens Exchange with a Trifocal Intraocular Lens in Patients with Presbyopia - Cindi K. Yim; Amisha Dave; Alyx Strawn; Jeffrey Chan; Irene Zhou; Dagny C. Zhu (Ophthalmology and Therapy, 2023)
Abstract Introduction Refractive lens exchange (RLE) patients represent a unique population with a different baseline and set of expectations compared to their cataract counterparts. Visual outcomes and patient satisfaction following RLE with bilateral implantation of a trifocal intraocular lens (IOL) were assessed in a cohort of patients with presbyopia and without cataract. Methods Charts of patients with presbyopia who underwent femtosecond laser-assisted RLE with bilateral implantation of the PanOptix trifocal IOL (toric and non-toric) at a single-surgeon, private practice center from September 2019 to August 2020 were retrospectively reviewed. Eyes with prior keratorefractive surgery, amblyopia, or underlying pathology were excluded. Primary endpoints included corrected and uncorrected visual acuity at distance (CDVA and UDVA), intermediate (DCIVA and UIVA), and near (DCNVA and UNVA) at 6 months. Secondary endpoints included residual refractive error, patient-reported satisfaction, spectacle independence, and visual disturbance profile as assessed by a validated questionnaire at 6 months. Results Seventy-eight eyes of 39 patients (mean age 56 ± 6 years; 79% female) were included. Most eyes were hyperopic (mean SE 2.35 ± 1.81). Postoperatively, 100% and 92% of eyes were within ± 1.00 D and ± 0.50 D of emmetropia, respectively. One hundred percent, 97%, and 97% of patients achieved UDVA, UNVA, and UIVA of logMAR 0.1 or better. Starbursts were the most frequent (67%) and bothersome (41%) visual disturbance cited, but nearly half (41%) of patients rated them as absent or “not bothersome at all.” Overall, 77% of patients reported achieving complete spectacle independence with 87% and 90% of patients stating they were satisfied with their vision and would recommend the same procedure to others, respectively. Conclusions RLE with bilateral implantation of the PanOptix IOL is a safe and effective procedure with good patient satisfaction. Because of their relatively clear native lenses and visually demanding needs compared to their cataract counterparts, surgeons should take extra precautions to counsel RLE patients on the limitations of trifocal technology.